Chemical kinetics data for the upper and lower atmosphere ; proceedings - 470717 Symposium on Chemical Kinetics Data for the upper and lower Atmosphere, Warrenton, Virginia, September 15-18, 1974; Benson, Sidney W. (New York : J Woliy, 1975)
42